O profissional de educação física adaptada em contextos não formais: expectativas e realidades em diferentes perspectivas - Francisco, Maloa de Fatima; Venditti Júnior, Rubens [UNESP] (My University, 2013)
This study aimed to comprehend the expectancies and realities in Adapted Motor Activities (AMA), of physical education (PE) professionals, public administration inside special institutions of people with disabilities (PwD), families of addicted people with disabilities and independent people with disabilities, living in Muzambinho City/MG/ Brazil, comparing the reality and expectation of EFA in non formal contexts. Participants were selected using criteria related to the central subjects of this research (PwD), totaling 26 individuals. Data were collected through interviews with audio recording and full transcription. It was found that the reality of APE has been moving in opposite ways than expectations, especially regarding the inclusion in non – formal contexts, starting the needing of reflections and discussions to acting in AMA and PE.

Este estudo teve por objetivo compreender as expectativas e realidades na atuação em Atividade Motora Adaptada (AMA) dos profissionais das áreas de Educação Física (EF), da administração pública das instituições especiais de atendimento às pessoas com deficiência (PcDs), familiares de PcDs dependentes e pelas PcDs independentes, residentes em Muzambinho/MG, comparando assim as expectativas e realidades da EFA em contextos não formais, sob estas diversas perspectivas de envolvimento. Os participantes foram selecionados por critérios relacionados aos sujeitos com deficiência destacados na pesquisa, totalizando 26 indivíduos. Os dados foram coletados através de entrevista com gravação em áudio e transcrição na íntegra. Foi verificado que a realidade da EFA atualmente se contrapõe às expectativas, principalmente no que tange à inclusão das PcDs nos contextos não formais, deflagrando a necessidade de reflexões e discussões para a atuação profissional em AMA e EF.
Adapted physical education teacher in non-formal contexts: expectations and realities through different perspectives
Keywords: Physical education; Adapted motor activity; People with disabilities; Inclusion; Teaching; Atividade motora adaptada; Pessoa com deficiência; Inclusão; Atuação profissional